2023
DOI: 10.3390/medicina59091560
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Targeting CGRP: A Novel Treatment in Vestibular Migraine

Andrea Lovato,
Caterina Disco,
Andrea Frosolini
et al.

Abstract: Background. Monoclonal antibodies (mAbs) directed against the calcitonin gene-related peptide (CGRP) or its receptor represented the first targeted and specialized approach to migraine prophylaxis. Nevertheless, they have been rarely considered in the treatment of vestibular migraine (VM). Our aim was to evaluate the effectiveness of anti-CGRP mAbs in VM patients who did not respond to conventional migraine treatments. Methods. Consecutive VM patients treated with erenumab were considered. As a comparison, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…All these treatments have undergone intense scrutiny for the treatment of migraine, however there is a paucity of data on their effectiveness for VM, as no randomized controlled trials of these therapies exist. However emerging evidence suggests that these CGRP antagonists may be beneficial for VM in the same way they are effective for migraine headache [ [39] , [40] , [41] ]. In the author's experience, when patients have failed other migraine therapies, these appear anecdotally to be an effective option.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…All these treatments have undergone intense scrutiny for the treatment of migraine, however there is a paucity of data on their effectiveness for VM, as no randomized controlled trials of these therapies exist. However emerging evidence suggests that these CGRP antagonists may be beneficial for VM in the same way they are effective for migraine headache [ [39] , [40] , [41] ]. In the author's experience, when patients have failed other migraine therapies, these appear anecdotally to be an effective option.…”
Section: Vestibular Migrainementioning
confidence: 99%
“…Early studies targeting CGRP with olcegepant have led to the development of improved "gepants" and monoclonal antibodies that can block either the CGRP receptor or the peptide. Numerous treatment options for migraines based on antagonizing CGRP signaling have been investigated in clinical trials, many of which have been approved by the FDA since 2018, and a few studies have indicated that CGRP antagonists have been successful in treating vestibular migraines, particularly in a subset of patients 19, 20 . Alternative treatments, such as vestibular suppressants, have not been shown to alleviate vertigo and may cause drowsiness 2123 .…”
Section: Introductionmentioning
confidence: 99%